Law Enforcement Against Illegal Logging that Occurs in the Forest Area of Kwala Sefruh Village - Joe Van Rajs Hutabarat; Selfiei Helfianto Simarmata; Suci Ramadani (International Journal of Sociology and Law, 2025)
Illegal logging is a form of environmental crime that has a serious impact on forest destruction, loss of biodiversity, and disruption of ecosystem balance. This study aims to analyze law enforcement efforts against illegal logging practices in the Kwala Serapuh Village Forest area. The method used in this study is an empirical juridical approach with data collection through interviews, field observations, and documentation. The results of the study show that despite the existence of regulations governing forest protection, law enforcement still faces various obstacles such as weak supervision, limited resources of law enforcement officials, and the involvement of individuals in these illegal practices. Efforts made include taking action against perpetrators, increasing patrols, and empowering communities around the forest. However, the effectiveness of law enforcement still needs to be improved through inter-institutional synergy, strengthening the capacity of the apparatus, and increasing community participation. This study concludes that law enforcement against illegal logging in the Kwala Serapuh Village Forest is still not optimal and requires a more comprehensive approach.